Total Facilities Management - Atkin, Brian; Brooks, Adrian (Oxford : Blackwell, 2005)
Bridging the gap between the theory of facilities management and its implementation, this book raises issues which all practitioners should consider before embarking on a particular plan.
Previous ed.: 2000.
Includes bibliographical references (p. 234) and index.
Keywords: Facility management; Business and Management